Process of Investigation onCriminal Actions of Fake Reports by the Reserse & Criminal Unit Investigators to Prosecutor - Rizki Andika Putra; Aryani Witasari; Deny Suwondo (Law Development Journal, 2022)
The aim of this research is to find out and analyze the process of investigating criminal acts of false reports by investigators from the Criminal Investigation Unit to the prosecutor's office. To find out and analyze the obstacles to the process of investigating criminal acts of false reports by investigators from the Criminal Investigation Unit to the prosecutor's office. To find out and analyze efforts to overcome obstacles to the process of investigating criminal acts of false reports by investigators from the Criminal Investigation Unit to the prosecutor's office. This study uses a sociological juridical approach, with descriptive analytical research specifications. The data used in this research is secondary data obtained through literature study which is then analyzed qualitatively. The results of this study are the Process of Investigating False Reports by Criminal Investigation Unit Investigators to the Prosecutor's Office is an investigator who submits a case file or the result of the report turns out to be false to the prosecutor's office, the prosecutor can return the case file or the results of the report to the investigator with instructions or directions from the prosecutor. Its office with coordination or cooperation between the police and the prosecutor's office. The resistance is the investigation of a criminal act of a false report takes a long time: in handling a criminal act of a false report by a defendant, it cannot be processed further if it only relies on information/confessions from the suspect, and if the case related to the crime of a false report has not been revealed or proven. Proving is difficult, it is difficult to prove the case in the investigation because in fact this case does not exist so that investigators must be more observant and patient in every collection of evidence. The solution is intensify every report or input from everyone about everything related to the problem of the crime of the false report. Increased awareness of new modes of crime.